Atomic Force Microscopy of Side Wall and Septa Peptidoglycan From Bacillus subtilis Reveals an Architectural Remodeling During Growth - Li, Kang; Yuan, Xiao-Xue; Sun, He-Min; Zhao, Long-Sheng; Tang, Ruocong; Chen, Zhi-Hua; Qin, Qi-Long; Chen, Xiu-Lan; Zhang, Yu-Zhong; Su, Hai-Nan (Frontiers in Microbiology, 2018)
Peptidoglycan is the fundamental structural constituent of the bacterial cell wall. Despite many years of research, the architecture of peptidoglycan is still largely elusive. Here we report the high-resolution architecture of peptidoglycan from the model Gram-positive bacterium Bacillus subtilis. We provide high-resolution evidence of peptidoglycan architecture remodeling at different growth stages. Side wall peptidoglycan from B. subtilis strain AS1.398 changed from an irregular architecture in exponential growth phase to an ordered cable-like architecture in stationary phase. Thickness of side wall peptidoglycan was found to be related with growth stages, with a slight increase after transition to stationary phase. Septal disks were synthesized progressively toward the center, while the surface features were less clear than those imaged with side walls. Compared with previous studies, our results revealed slight differences in architecture of peptidoglycan from different B. subtilis strains, expanding our knowledge about the architectural features of B. subtilis peptidoglycan.